The Accuracy of 0.3 Tesla MRI for Diagnosing Meniscal Tears in the Knee a Multi-Center Study - Erum Habib, Faiz Ul Aziz, Nasir Ali, Muhammad Yaseen, Mian Javed Iqbal, Shah Abdur Rahim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to compare the accuracy of a 0.3-tesla MRI in diagnosing meniscal injury in the knee to that arthroscopic findings. Duration and place of study Qazi Hussain Ahmad Medical Complex Nowshera, Pakistan, from Jan 2021 to Jan 2022. (departments of Radiology and Orthopedic). Methodology: One hundred patients who satisfied the study’s inclusion criteria were sent from the orthopedics. We successfully collected patient data and permission from the Qazi Hussain Ahmed Medical Complex Nowshera. outpatient department and tertiary care hospital kpk between January 2021 and January 2022. All of the 0.3 Tesla scans were completed by a single MRI tech. To confirm the findings of the MRI, an arthroscopy was done by a professor of orthopedics. We tracked everything in a proforma spreadsheet and analyzed the data. Results The result is that 100 patients participated in the trial. There were 96 males (or 95%) and four females (5%). Individuals’ ages varied from the low teens to the high fifties. Patients had a mean age of 30.3 +/- 6.82 years. We found that, in contrast to arthroscopy, our method for diagnosing meniscal injuries of the knee joint was susceptible (96%), specific (95%), and accurate (95%). Conclusion:For the evaluation of meniscal injuries, MRI is a reliable, accurate, and noninvasive method. Keywords: Arthroscopy, MRI, and Knee Replacement are Some Key Terms